Toward AI"‘Infused ELT in the Indonesian Context: A Needs Analysis for a Digital"‘Literacy Course - Tatipang, Devilito Prasetyo; Iskandar, Iskandar; Alrajafi, Gali; Liando, Nihta Vera Frelly; Wuntu, Ceisy Nita; Budiman, Jeihn; Ganap, Nindy Nource (Journal of English Education Program, 2025)
This study explores the integration of Artificial Intelligence (AI) in English Language Teaching (ELT) and its impact on enhancing students"™ digital skills, specifically within the context of digital literacy. Utilizing a questionnaire and interviews with students, the research examines perceptions regarding the necessity and relevance of AI in digital literacy learning. Findings indicate that a significant majority of students recognize the benefits of AI, including improved digital literacy, increased confidence in understanding technology, enhanced critical thinking skills, and greater creativity. Specifically, 64% of respondents reported that AI usage helps them improve their digital literacy skills, while 60% expressed heightened confidence in navigating digital technologies. However, challenges remain, with many students noting difficulties in adjusting to AI tools, emphasizing the need for adequate support and training. The results align with existing literature that highlights the potential of AI to personalize learning experiences and foster critical analysis among students. Despite the positive feedback, it is crucial to address the challenges associated with AI integration to ensure that all students can fully benefit from these advancements. Recommendations for educators include developing comprehensive training programs, providing ongoing support, and fostering a learning environment that encourages exploration of AI technologies. Overall, this study underscores the transformative potential of AI in ELT, offering insights into its role in preparing students for the demands of the digital age while highlighting the importance of supportive frameworks for effective implementation.